AGROFORESTRY IN THAILAND PERSPECITIVE OF FOREST INDUSTRY ORGANIZATION (FIO) - Phothitai, Montee (วารสารวนศาสตร์ไทย, 2022)
Nearly 80% of the country’s 52 million people live on agricultural earning. Most of forest land is illegally cleared for agricultural purposes. Especially shifting cultivation, one of the most serious problems in forest destruction. The modified taungya system, one known form of agroforestry, has been applied by the FIO. to successfully solve these problems. Agroforestry systems carried out by the FIO. are: a) Forest trees and agricultural crops where families in forest villages of the FIO., excluding those in the South, cultivated agricultural crops, combined with forest trees. b) Forest trees and horticultural crops where the FIO.’s forest villagers in the South chose horticultural crops like coffee, rubber tree and cashew nut combined with forest trees. c) Animals and trees: cattle raising and bee keeping are maintained by FIO.’s plantations in all regions as extension programs.